TINJAUAN KEWENANGAN JAKSA PENUNTUT UMUM DALAM MELAKUKAN PENUNTUTAN TERHADAP SUATU TINDAK PIDANA MELALUI PROSES PENGADILAN - Fijriya, Ika; Mukhammad, Hafis (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2024)
The authority of the Public Prosecutor in prosecution is contained in the Criminal Procedure Code (KUHAP). The role of the prosecutor is important to achieve the goals of the criminal justice system and overcome criminal acts in society. By using research methods, library research methods or literature by collecting various sources and comparing them with other sources. It can be concluded that the prosecutor must process the results of the investigation within 7 days, determine the completeness of the files, and inform the National Police. If the file is incomplete, the prosecutor will return it to be completed in the pre-prosecution process. In this case, several factors such as a lack of evidence or the absence of a criminal offense may lead to the termination of the prosecution. Efforts to overcome this problem involve the establishment of a coordination forum between the National Police and the Public Prosecutor, legal discovery in the Criminal Procedure Code, as well as combining the investigative function in Prosecution in Connection with Future Legal Arrangements.